2016
DOI: 10.2174/1574884711666160813231352
|View full text |Cite
|
Sign up to set email alerts
|

Ethosomes as Vesicles for Effective Transdermal Delivery: From Bench to Clinical Implementation

Abstract: From various research reports, it can be concluded that ethosomes are the competent and efficient vesicles to provide better drug transport via transdermal route.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Up to a concentration of 40%(v/v), the %EE increased which can be attributed to the increased uidity of the ethosomal membrane and also due to increased solubility of the lipophilic drug in the inner polar ethosomal core. But when ethanol concentration was above 40%(v/v), the %EE decreased due to increased solubilisation of the drug in ethanol causing disruptions in the vesicular membrane (27,28), This was a contradicting the effect from the normal, which can be reasoned to increase in the uidity of the membranes thereby the entrapped drug leaching out (29).…”
Section: Discussionmentioning
confidence: 99%
“…Up to a concentration of 40%(v/v), the %EE increased which can be attributed to the increased uidity of the ethosomal membrane and also due to increased solubility of the lipophilic drug in the inner polar ethosomal core. But when ethanol concentration was above 40%(v/v), the %EE decreased due to increased solubilisation of the drug in ethanol causing disruptions in the vesicular membrane (27,28), This was a contradicting the effect from the normal, which can be reasoned to increase in the uidity of the membranes thereby the entrapped drug leaching out (29).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they have superior pharmaceutical properties, including stability at room temperature, high entrapment efficiency, and improved compatibility with the stratum corneum, thus promoting the effective penetration of lipophilic drugs into the skin. [12][13][14] In our preliminary study, we have proven that ethosomes can promote transdermal permeation of lipophilic drugs, such as lidocaine, with a shorter onset time and a longer duration in vivo than lidocaine-based liposomes or lidocaine delivered in a hydroethanolic solution. 15 Subsequently, ethosomes have been used in photodynamic therapy, 16,17 cosmeceuticals, 18 and a vaccine.…”
Section: Introductionmentioning
confidence: 93%
“…[29][30][31] In terms of possible mechanisms for ethosomes to promote percutaneous permeation of drugs, two viewpoints have been presented: the first one is that ethanol is a known penetration enhancer, which can disturb the multilamellar and ordered lipid domain, lower the structure density, and enhance the fluidity of the stratum corneum, thus providing the vesicles with flexible characteristics that allow them to penetrate easily into deeper layers of the skin; 32,33 the second one is that phospholipids between the stratum corneum and ethosomal vesicle fuse easily, thus changing the transition temperature, leading to enhanced drug penetration. 34 In our research, we interestingly found that even though the lipid content in the liposomes and the ethanol content in the hydroethanolic solution were equal with those in the ethosomes, after percutaneous penetration, a greater fluorescence intensity in the skin of the ethosomal system was observed, compared with that in the hydroethanolic solution and liposomes (P,0.05; Figure 2B).…”
mentioning
confidence: 99%
“…It may contain 2%-5% phospholipids and 20%-40% ethanol (Grath and Uitto, 2008). Drug penetration through the skin is higher in the case of ethosomes as compared to liposomes due to the ability of ethanol to fluidize the membrane lipids of SC (Akhtar et al, 2016;Blume et al, 1993;Romero and Morilla, 2013). The addition of ethanol increases the particle size of ethosomes, and a decrease in size was observed by maintaining a constant concentration of phospholipid (Campani et al, 2016).…”
Section: Ethosomesmentioning
confidence: 99%